1997
DOI: 10.1046/j.1365-2141.1997.3113127.x
|View full text |Cite
|
Sign up to set email alerts
|

Continuing (maintenance) therapy in lymphoblastic leukaemia: lessons from MRC UKALL X

Abstract: Summary.The relationship between the prescribed dose of drugs during continuing (maintenance) therapy, the degree of marrow suppression caused, and subsequent event-free survival was examined in a cohort of 740 children with lymphoblastic leukaemia treated on MRC UKALL X. Girls, younger children, and patients who had received intensification treatment, were prescribed lower doses of mercaptopurine, became neutropenic more readily, and had more interruptions of treatment. Children who had one or more episodes o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
32
0

Year Published

2000
2000
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(32 citation statements)
references
References 17 publications
0
32
0
Order By: Relevance
“…A number of basic aspects has been considered including the use during induction of 40 mg/m 2 /day of prednisolone rather than 60 mg/m 2 ; the lack of use of dexamethasone; the dropping of daunorubicin from induction, the potentially sub-optimal route of administration (s.c.), dosage, and scheduling of asparaginase, the presence of a gap to allow recovery of normal marrow following early intensification between weeks 5 and 8 (and again between weeks 20 and 23), as a result of the form of intensification used in UKALLX and XI, and a possible lack of intensive and strict compliance with delivery of continuation therapy to the patient. Chessells et al 23 demonstrated that children in UKALLX with one or more episodes of neutropenia with a count of Ͻ0.5 × 10 9 /l had an improved prognosis compared with those who never became neutropenic. Whether neutropenia or lymphopenia induced by continuation therapy is the best guide of efficacy remains unclear, but it is certain that to be successful certainly for most childhood ALL, therapy must be of 2-3 years duration and induce significant immunosuppression.…”
Section: Figurementioning
confidence: 99%
“…A number of basic aspects has been considered including the use during induction of 40 mg/m 2 /day of prednisolone rather than 60 mg/m 2 ; the lack of use of dexamethasone; the dropping of daunorubicin from induction, the potentially sub-optimal route of administration (s.c.), dosage, and scheduling of asparaginase, the presence of a gap to allow recovery of normal marrow following early intensification between weeks 5 and 8 (and again between weeks 20 and 23), as a result of the form of intensification used in UKALLX and XI, and a possible lack of intensive and strict compliance with delivery of continuation therapy to the patient. Chessells et al 23 demonstrated that children in UKALLX with one or more episodes of neutropenia with a count of Ͻ0.5 × 10 9 /l had an improved prognosis compared with those who never became neutropenic. Whether neutropenia or lymphopenia induced by continuation therapy is the best guide of efficacy remains unclear, but it is certain that to be successful certainly for most childhood ALL, therapy must be of 2-3 years duration and induce significant immunosuppression.…”
Section: Figurementioning
confidence: 99%
“…[4][5][6][7] This variance is only partially explained by patient factors including comorbidity, age and individual chemotherapeutical pharmacokinetics and pharmacodynamics. 8 Genetic variance may also contribute to the risk of developing neutropenia during chemotherapy, but to date this possibility has not been investigated. A candidate gene that might be associated with the risk of developing chemotherapy-induced neutropenia is Toll-like receptor 4 (TLR4), as TLR4 has been shown to have a role in inhibition of neutrophil apoptosis, and extension of the functional lifespan of neutrophils during stimulation with lipopolysaccharide.…”
Section: Introductionmentioning
confidence: 99%
“…In the past 2 decades, the cure rate for ALL has dramatically increased, 1 and much of this success can be attributed to improved stratification of tumors paired with finely tuned treatment protocols. [1][2][3] Further improvements in the cure of this disease, however, are hampered by a lack of understanding of molecular variability among tumors and targets for the further individualization of treatment. Treatments directed toward specific biologic pathways involved in leukemia pathology not only may improve outcome for some patients but may also reduce the toxicity and nonspecificity associated with conventional chemotherapeutic agents.…”
Section: Introductionmentioning
confidence: 99%